Performance and Operational Strategies Evaluation for Electric Chillers at UTP GDC Plant - Chia , Calvin Sze Ming (IRC, 2018)

(untitled)
Chillers are widely used worldwide for extensive cooling of large spaces such as plants, industrial facilities, airports and even universities. The paper presents a study on the performance of four electric chillers available at the Universiti Teknologi Petronas Gas District Cooling (GDC) Plant during peak and off-peak period and the modelling of the optimal operational strategies for each of the electric chillers. Performance of all electric chillers were analysed through the calculation of the coefficient of performance (COP) of all chillers. Graphical analysis and relative comparison were utilized to formulate the best strategy for each electric chiller and to formulate the best strategy available as a whole. The formation and implementation of the strategy was expected to improve overall efficiency of the electric chillers as well as reduces the operational cost.